2022
DOI: 10.18502/ijrm.v20i1.10405
|View full text |Cite
|
Sign up to set email alerts
|

The association between fetal renal artery indices in late pregnancy and birth weight in gestational diabetes mellitus: A cohort study

Abstract: Background: Estimation of the fetal birth weight and diagnosis of small for gestational age in the fetuses of women with gestational diabetes mellitus (GDM) are currently imprecise. Objective: We aimed to evaluate the association between fetal renal artery Doppler indices and neonatal birth weight in women with GDM in late pregnancy. Materials and Methods: This cohort study recruited 246 pregnant women from Shariati Hospital in Tehran, Iran, in two GDM and healthy control groups. Participants under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…One similar study conducted showed potential correlation between RA indices and perinatal outcome [27]. Another study showed early detection of hypoxic fetuses using RA hemodynamics in patients with gestational diabetes mellitus [28]. One significant limitation of our study was the limited number of patients with polyhydramnios leading to insufficient evaluation of RA indices.…”
Section: Discussionmentioning
confidence: 92%
“…One similar study conducted showed potential correlation between RA indices and perinatal outcome [27]. Another study showed early detection of hypoxic fetuses using RA hemodynamics in patients with gestational diabetes mellitus [28]. One significant limitation of our study was the limited number of patients with polyhydramnios leading to insufficient evaluation of RA indices.…”
Section: Discussionmentioning
confidence: 92%
“…When pregnancy is complicated by diabetes, renal blood perfusion levels increase. When end-diastolic blood flow is blocked in RA, the S/D level enhances, which indicates the level of fetal renal blood flow, leading to the reduction of urine volume and amniotic fluid volume, then forming intrauterine hypoxia [ 24 , 25 ]. The results suggested that the RI, PI, and S/D levels of fetal UA in GDM patients were evidently enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…The green squares represent each study individual SMD and the extending lines the 95% confidence intervals. The black diamond represents the overall estimate result [ 18 , 21 , 32 , 34 , 36 , 39 , 53 , 56 , 60 , 61 , 80 , 82 , 83 ].…”
Section: Figurementioning
confidence: 99%
“…The UA-RI, UtA-PI, and UtA-S/D ratio were significantly higher in diabetic in contrast to non-diabetic pregnancies (SMD = 0.40, 95%CI = 0.07-0.73, p = 0.020 (Figure 2); SMD = 1.62, 95%CI = 0.36-2.88, p = 0.010 (Figure 3), and SMD = 1.02, 95%CI = 0.02-2.03, p = 0.050 (Figure 4), respectively). [18,21,32,34,36,39,53,56,60,61,80,82,83]. [18,21,32,34,36,39,53,56,60,61,80,82,83].…”
Section: Meta-analysismentioning
confidence: 99%